OPTIMUM LENGTH OF RAISING TIME AND THE RELATION WITH BUSINESS INCOME OF SIMMENTAL-ONGOLE GRADE CROSSBRED BEEF CATTLE FATTENING FARM IN WONOSOBO REGENCY-CENTRAL JAVA - Setiawan, B.M.; Isbandi, I.; Santosa, P.B.; Rianto, E. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
Optimizing the length of raising time in cattle fattening business should be applied to increasefarmers’ income. A survey research was carried out to analyze the optimum raising duration and itsrelationship with income in the business of Simmental - Ongole Grade crossbred (SOG) beef cattlefattening. This research involved 50 farmers chosen purposively as respondents based on some specificcriteria, i.e. the farmers had been experienced at least for 5 years, the business scale was 1 – 3 bulls andthe cattle’s live weight was around 250 – 350 kg. Data were taken by cross section and time series for 3months, covering respondents’ identity, cattle business condition, business inputs, cattle’s weight, inputand output prices. The data were analyzed using combined data regression model. The optimum raisingduration was calculated using profit function per time, while the inputs were converted into timefunction. All of the costs and incomes of business were calculated. The results showed that the optimumraising duration of SOG beef cattle fattening was reached at the 1.5 months from the cattle aging 16.67months old. The amount of the total cost, revenue and income in the optimum raising duration were IDR7,161,740.00; IDR 7,797,100.00 and IDR 635,350.00, respectively. The amount of the cost, revenue andincome in the optimum raising duration per kg of cattle live weight, were IDR 23,247.00; IDR25,157.00 and IDR 1,910.00, respectively.